1993
DOI: 10.1002/mpo.2950210202
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar rhabdomyosarcoma with the t(2;13): Cytogenetic findings and clinicopathologic correlations

Abstract: We describe here the clinical and pathologic features associated with a specific translocation, t(2;13), in alveolar rhabdomyosarcoma. Tumor specimens from 14 patients with a t(2;13)-positive alveolar rhabdomyosarcoma were studied for cytogenetic-clinicopathologic correlations. Three patients had occult primary tumors; nine patients had primary tumors of the trunk (mediastinal, pelvic, or rectal). The presence of the t(2;13) was ascertained from examination of tumor involved bone marrow in ten patients who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Previous studies (Douglass et al, 1993) to define the role of reciprocal translocations in rhabdomyosarcoma have been limited by difficulties in establishing karyotypes and by the limited availability of frozen tissue for FISH or RT-PCR. We have developed an RT-PCR assay, which works on formalin-fixed tissue (Anderson et al, 1997) and allows a more extensive study of archival material from patients for whom there are detailed data of treatment and outcome.…”
mentioning
confidence: 99%
“…Previous studies (Douglass et al, 1993) to define the role of reciprocal translocations in rhabdomyosarcoma have been limited by difficulties in establishing karyotypes and by the limited availability of frozen tissue for FISH or RT-PCR. We have developed an RT-PCR assay, which works on formalin-fixed tissue (Anderson et al, 1997) and allows a more extensive study of archival material from patients for whom there are detailed data of treatment and outcome.…”
mentioning
confidence: 99%
“…In MFH, 19p 13 abnormalities have been associated with a higher rate of local recurrence and with metastases, trisomy 8 more often occurs in relapsing MFH, whereas presence of ring chromosomes has been associated with a lower tendency for tumor relapse (Choong et al 1996, Mandahl 1996. In alveolar rhabdomyosarcomas, an association was found between t(2; 13) and older patient age and truncal location, but the genetic change did not seem to influence the tumor response rate after treatment (Douglass et al 1993 ). Reduced expression of the RBI protein have been detected more often in metastatic sarcomas (Cance et al 1990) and an increased expression of the TP53 and MDM2 proteins have been shown to correlate with poor survival (Cordon-Cardo et al 1994 ).…”
Section: Diagnostic Prognostic and Therapeutic Possibilitiesmentioning
confidence: 94%
“…2 RMS are distinguished from other soft tissue sarcomas by immunohistochemical reactivity for the striated muscle-specific markers desmin, MYOD1 and muscle-specific actin. 2 ARMS generally presents in adolescents, 3 most commonly originating in the muscle tissue of the extremities. 4 Criteria for subtyping ARMS include physical location of the tumor, its alveolar appearance and the great majority express the PAX3-FOXO1 (PAX3-FKHR) chimeric gene, resulting from the in-frame fusion between chromosomes 2 and 13.…”
Section: Introductionmentioning
confidence: 99%